Industrial Forestry Negatively Affects Small-Farms Honey Production in South-Central Chile: Evidence from a Landscape Scale - Vergara-Egert, P; Moreira-Arce, D; Alaniz-Baeza, A; Carvajal-Leon, M (Taylor and Francis Ltd., 2024)
Land use and cover change have a high influence on bee species, where honey bees (Apis mellifera) could be affected in terms of resources, dispersal, and habitat. However, the influence of landscape context on honey productivity has been scarcely explored in comparison with population parameters, which is an essential topic for the economic development of rural communities based on apiculture. Here, we tested the hypothesis if honey production decreases with the increase of exotic forest plantations in the landscape as the cover of native forest decreases, vegetation and soils become increasingly degraded. We compiled data on honey productivity for two years (2018 and 2019) of small-scale honey production in 17 landscapes of 1 km radii (Curanilahue state in south-central Chile). Then, the landscapes were characterized by using remote sensing techniques, including biophysical and compositional landscape variables. Finally, Generalized Linear Mixed Models were implemented to explore the relationship between landscape variables and honey productivity. We identified a positive relationship between honey productivity with built cover and grassland cover. On the other hand, a negative relationship was found between honey production and net primary production, exotic forest plantations, and tree senescence index. Our results provide new insights into the landscape-scale drivers of hive productivity in rural landscapes of south-central Chile. © 2023 International Bee Research Association.